The response of precast concrete segmental columns subjected to near base impact - Zhang, Xihong; Hao, Hong (2019)
Precast concrete segmental column has attracted many attentions for the past decades due to its unique features especially in improving the construction quality and efficiency. However, the performance of precast segmental column under lateral impact loading has been less studied. Our previous studies performed laboratory pendulum impact tests on scaled segmental columns to investigate their behaviours when impacted at mid-span of the column. This article studies the response of segmental column when impacted near the column base, which generates different response modes and failure mechanisms compared to the columns subjected to the mid-span impact. Lateral impacts are applied either to segmental joint between the two bottom segments or directly onto the centre of the base concrete segment. A detailed three-dimensional numerical model is created and validated with laboratory impact testing results on scaled segmental columns. A full-scale 3-m tall segmental column is then numerically built to study the behaviour under near base impact. The column damage and failure modes are analysed. The influences of prestress level in the post-tensioning tendon and concrete strength on the performance of segmental column subjected to near base impacts are investigated through numerical simulations.